Analisis Tingkat Kepuasan Mahasiswa Terhadap Sistem Informasi Akademik Universitas Cokroaminoto Palopo - Nur Tri Irawan; Indra Jaya Saputra (STMIK Amika Soppeng, 2022)
This study discusses the influence of the results of the analysis of satisfaction levels on interest indicators, system indicators, information indicators, and student service quality at UNCP Siakad. This research is descriptive quantitative. The population of this research is the faculty of computer engineering, faculty of agriculture, and faculty of science and the total number of respondents is 697 respondents. Data were analyzed using cross- tabulation statistical analysis followed by descriptive statistics. The conclusions from this study are (1) the level of student satisfaction with the uncp siakad is in the satisfied category. (2) the level of student satisfaction with the uncp siakad for interface from each faculty is in the satisfied category. (3) the level of student satisfaction with the uncp siakad for system quality indicators from each faculty is in the satisfied category, (4) the level of student satisfaction with uncp siakad for information quality indicators from each faculty is in the satisfied category (5) the level of student satisfaction with uncp siakad for quality indicators services from each faculty are in the satisfied category.